Community Based Forest Management Strategies and Projections In KPH XIX Saka South Oku, South Sumatera - Enda Kartika Sari; Andy Mulyana; Mirza Antoni; Dessy Adriani (Program Pascasarjana Universitas Sriwijaya, 2022)
In accordance with the mandate of the law, forests are part state-controlled and must be managed sustainably, for that the existence of KPH is a necessity for all parties. Forest management is generally realized based on forest governance, management plans, forest rehabilitation, forest protection, and conservation. To improve people's welfare, it is necessary to make optimal use of forest areas to support the preservation of natural resources and overcome global climate change. This research was carried out in KPH Unit XIX Saka, South OKU Regency which is located in the forest group of HL Saka, HPT Saka, and HP Saka, South OKU Regency. Data presentation was carried out descriptively and analyzed using the SWOT method. The results of the study show that KPH as a forest area manager at the site level can guarantee the continuity of forest area functions by implementing sustainable forest management with forest ecological values, based on community welfare. The strategy adopted is the SO Strategy, namely by utilizing and promoting the potential of forest resources, especially non-timber forest product resources (HHBK), and the potential for forest environmental services in the KPH.